2022
DOI: 10.1038/s41598-022-10370-1
|View full text |Cite|
|
Sign up to set email alerts
|

An open label randomized clinical trial of Indomethacin for mild and moderate hospitalised Covid-19 patients

Abstract: Indomethacin, a non-steroidal anti-inflammatory drug (NSAID), has been presented as a broad-spectrum antiviral agent. This randomised clinical trial in a hospital setting evaluated the efficacy and safety of this drug in RT-PCR-positive coronavirus disease 2019 (COVID-19) patients. A total of 210 RT-PCR-positive COVID-19 patients who provided consent were allotted to the control or case arm, based on block randomisation. The control arm received standard of care comprising paracetamol, ivermectin, and other ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…An open-label randomised clinical trial in India evaluated the efficacy and safety of indometacin for patients hospitalised with COVID-19 with mild to moderate symptoms including fever, cough, and myalgia at admission. 90 None of the 103 patients randomly assigned to indometacin developed desaturation (SpO 2 ≤93%); however, desaturation did occur in 20 of the 107 patients allocated to paracetamol. Patients who received indometacin also had more rapid symptom relief than those given paracetamol, with most symptoms disappearing in half the time.…”
Section: Other Nsaids For Early Stage Covid-19mentioning
confidence: 94%
“…An open-label randomised clinical trial in India evaluated the efficacy and safety of indometacin for patients hospitalised with COVID-19 with mild to moderate symptoms including fever, cough, and myalgia at admission. 90 None of the 103 patients randomly assigned to indometacin developed desaturation (SpO 2 ≤93%); however, desaturation did occur in 20 of the 107 patients allocated to paracetamol. Patients who received indometacin also had more rapid symptom relief than those given paracetamol, with most symptoms disappearing in half the time.…”
Section: Other Nsaids For Early Stage Covid-19mentioning
confidence: 94%
“…In line with this hypothesis, another paper showed that celecoxib could both prevent disease progression and promote recovery from COVID-19, whereas ibuprofen was less effective (Hong et al, 2020). Protective effects against COVID-19 were also shown for indomethacin or aspirin (Fazio et al, 2021;Perico et al, 2022;Ravichandran et al, 2022).…”
Section: Introductionmentioning
confidence: 81%
“…Based on these pathophysiological mechanisms of the disease, various multidrug approaches were proposed for early outpatient treatment of mild COVID-19 [ 3 , 4 , 6 , 7 ]. Nonsteroidal anti-inflammatory drugs (NSAIDs) administered at the beginning of the symptoms have shown to significantly reduce hospitalization and disease duration in observational studies [ 3 - 5 , 9 ] and in a small open-label RCT [ 10 ]. While waiting for more solid evidence and generally approved guidelines, many GPs decided to treat outpatients at the first stage of the disease with commonly available over-the-counter drugs that had been previously suggested to prevent the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%